Evaluating actual speed against the permissible speed of vehicles during free-flow traffic conditions - Mohd Azwari, Nur Farhanatul Syasya; Kadar Hamsa, Abdul Azeez (Universiti Kebangsaan Malaysia, 2021)
It is commonly seen that vehicles were moving above the speed limit on many expressways especially during free-flow traffic conditions. To ensure safe movement of vehicles, it is important to compare the actual speed of the vehicles against the posted speed limit. The main purpose of this paper is to evaluate and compare the actual speed of the vehicles with the allowable speed limit during free-flow traffic conditions. Duta-Ulu Kelang Expressway (DUKE) was selected as a case study. Major data were collected by using road geometrical survey and spot speed survey method. Around 400 vehicles’ speed were measured at a selected road stretch for 4 hours during off-peak period. Systematic sampling technique was used to select samples from the targeted vehicle population. Descriptive statistical methods were used to analyze the speed trends and speed characteristics of the sampled vehicles. T-test was applied to test the actual speed between each selected hour and to test the differences between actual average vehicle speed and allowable speed limit for statistical significance. The results show most of the vehicles (66%), on average, were moving at a speed higher than the allowable speed limit of 90 km/h. The differences between actual average speed and allowable speed limit were tested for statistical significance which as a result indicates a clear difference between actual average speed and allowable speed limit. Few recommendations are drawn to discourage excessive speed in order to make the roads free from accidents and to improve the safety of the road users.